2013
DOI: 10.4028/www.scientific.net/amr.747.463
|View full text |Cite
|
Sign up to set email alerts
|

Cure Characteristics, Morphology and Mechanical Properties of Partially Cured NBR Blended with NR

Abstract: This research is aimed to study the effect of partially cured acrylonitrile butadiene styrene rubber (NBR) blended with natural rubber (NR) and vulcanized with sulfur system. The research started with compounding NBR with zinc chloride, ZnCl2 in an internal mixer. The cure characteristic of the NBR compound was investigated using moving die rheometer (MDR). The compound NBR is then blended in NR at 160 °C. The temperature was then lowered to 50 °C before the addition of sulfur cure additives. Cure characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, sample CPI-25/NBR-75 seems to more compatible morphology than sample CPI-75/NBR-25 as also exhibited by mechanical and thermal properties of these blends. Although CPI/NBR blends have multi-phase morphology [4,5,30] but here NBR has low acrylonitrile content with nearly similar viscosity to CPI which might be responsible for compatibility [31] of both the materials. Thus, morphology studies revealed that CPI/NBR blends are miscible (homogeneous) which is also confirmed by the dynamic mechanical measurements (glass transition temperature) of this article.…”
Section: Morphologymentioning
confidence: 99%
“…However, sample CPI-25/NBR-75 seems to more compatible morphology than sample CPI-75/NBR-25 as also exhibited by mechanical and thermal properties of these blends. Although CPI/NBR blends have multi-phase morphology [4,5,30] but here NBR has low acrylonitrile content with nearly similar viscosity to CPI which might be responsible for compatibility [31] of both the materials. Thus, morphology studies revealed that CPI/NBR blends are miscible (homogeneous) which is also confirmed by the dynamic mechanical measurements (glass transition temperature) of this article.…”
Section: Morphologymentioning
confidence: 99%